2004
DOI: 10.1021/bi036310m
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Mutagenesis Studies on the Phosphorylation Region of Human Cardiac Troponin I

Abstract: Phosphorylation of the cardiac troponin complex by PKA at S22 and S23 of troponin I (TnI) accelerates Ca(2+) release from troponin C (TnC). The region of TnI around the bisphosphorylation site binds to, and stabilizes, the Ca(2+) bound N-terminal domain of TnC. Phosphorylation interferes with this interaction between TnI and TnC resulting in weaker Ca(2+) binding. In this study, we used (1)H-(15)N-HSQC NMR to investigate at the atomic level the interaction between an N-terminal fragment of TnI consisting of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…ine, respectively. Previous studies have indicated that this is indeed the case with respect to interactions between the cTn subunits (12,29), Ca 2ϩ dissociation rates from cTnC (45), and pCa 50 (10). Moreover, it can be noted that we observed similar functional parameters in cells exchanged with dephosphorylated cTnI mimicked with alanine substitutions at Ser 23 and Ser 24 and unphosphorylated wild-type cTnI (Table 2).…”
supporting
confidence: 82%
“…ine, respectively. Previous studies have indicated that this is indeed the case with respect to interactions between the cTn subunits (12,29), Ca 2ϩ dissociation rates from cTnC (45), and pCa 50 (10). Moreover, it can be noted that we observed similar functional parameters in cells exchanged with dephosphorylated cTnI mimicked with alanine substitutions at Ser 23 and Ser 24 and unphosphorylated wild-type cTnI (Table 2).…”
supporting
confidence: 82%
“…The structural consequence of phosphorylation of cTnI on protein-protein interactions that occur within the cTn complex as well as conformational changes of cTnI have been extensively studied using NMR (22,23,26,39,40) and FRET (21,33,(41)(42)(43). These studies suggest that the N-terminal extension of cTnI, most likely the residues immediately before the PKA phosphorylation sites, interact with the N-domain of cTnC.…”
Section: Discussionmentioning
confidence: 99%
“…Ward et al (53) also showed that peptide residues 1-18 of cTnI do not bind to cTnC. NMR studies (53,54), as well as previous studies (37), demonstrated that PKA phosphorylation at Ser 23 and Ser 24 produced only localized structural effects in segment residues ϳ25-35.…”
Section: Phosphorylation Of Ctni: Cardiac-specific N-terminal Extensionmentioning
confidence: 91%